2014
DOI: 10.1007/s10792-014-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of three surgical methods of conjunctival autograft fixation in the treatment of pterygium

Abstract: Our aim primarily was to compare the recurrence rate with three techniques of conjunctival fixation (suture versus fibrin glue versus autologous in situ blood coagulum) over bare sclera following pterygium excision. Ninety eyes of 90 patients with primary pterygium were randomly divided into three groups: group I (30 eyes) underwent autografting and fixation with 8-0 vicryl sutures, group II (30 eyes) with fibrin glue and group III (30 eyes) with autologous in situ blood coagulum. The patients were reviewed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 23 publications
0
29
1
Order By: Relevance
“…Srinivasan et al, 19 in his study published in 2009 also found a higher recurrence rate with fibrin glue technique along with poor attachment, whereas Sati et al, 20 also conducted a similar study but reported contrary finding to our study and previous studies that graft loss and recurrence rate was similar in both techniques. He observed that the higher rate of graft rejection might be because of graft size rather than the technique of fixation.…”
Section: Discussioncontrasting
confidence: 77%
“…Srinivasan et al, 19 in his study published in 2009 also found a higher recurrence rate with fibrin glue technique along with poor attachment, whereas Sati et al, 20 also conducted a similar study but reported contrary finding to our study and previous studies that graft loss and recurrence rate was similar in both techniques. He observed that the higher rate of graft rejection might be because of graft size rather than the technique of fixation.…”
Section: Discussioncontrasting
confidence: 77%
“…CAG can be xed to bare sclera either by sutures, brin glue or autologous in situ blood coagulum. Amongst the three techniques of xing CAG, brin glue de nitely offers the advantage of least operative time 19 . SLET was rst used for the treatment of stem cell de ciency by Sangwan and coworkers 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Pterygium excision with CAG or CLAG is the method of choice for most surgeons. The results of recent studies indicate on 3-10% recurrence rate after CAG procedure (27)(28)(29) but it may range up to 30% (for recent review see 30). The limbal conjunctival autograft procedure seems to be a little more effective than CAG with recurrence rate varies between 0 and 15% (for recent review see 30) but this process requires more experience.…”
Section: Discussionmentioning
confidence: 99%